Етика земельних відносин при введенні кадастру - Мартинюк, А. (НУБіП України, 2025)
Abstract: During martial law, ethical issues in land relations become particularly significant. The challenges arising from military actions necessitate fairness, transparency, and effective land resource management. The implementation of the cadastre and the preparation of cadastral documentation are crucial aspects of land administration, ensuring land registration, accounting, and usage control. However, in wartime, this process becomes more complicated due to infrastructure destruction, population displacement, and document loss. Additionally, instability increases the risk of unlawful actions such as unauthorized land occupation or cadastral data manipulation. Ethical land cadastre management is based on several key principles. First, transparency is essential to minimize the possibility of data manipulation. Second, the principle of equality must be upheld to protect every citizen’s land rights regardless of social status or political influence. Third, objectivity and impartiality in decision-making regarding land issues must be ensured. Special attention should be given to protecting the rights of internally displaced persons (IDPs) regarding land ownership. They often face discrimination or lack of access to cadastral data, complicating their ability to exercise their rights. Ethical land relations also imply professional responsibility for specialists working in cadastral management. Their work should be guided not only by legal norms but also by integrity, prioritizing long-term community and state interests. In conclusion, an ethical approach to cadastre management during martial law is crucial for maintaining legal stability and public trust in the state. It requires all stakeholders in land relations to act responsibly, adhere to the law, and adopt a balanced approach to conflict resolution.
Ethics of land relations in the implementation of cadastre
Keywords: кадастр; воєнний стан; земельне право; cadastre; martial law; land law